Post Operative Deep Vein Thrombosis: A Study of 150 Cases (Journal of Chittagong Medical College Teachers' Association, 2016)
Thromboembolism is a wide spectrum entity of which post operative Deep Vein Thrombosis (DVT) is a part. At present there is inadequate information available regarding the incidence of DVT in Bangladesh. The aim of this cross-sectional study was to see the incidence of postoperative DVT at BIRDEM Hospital from March to December 2008. It was performed on 150 patients who had any operation of more than one hour of duration. Among 150 patients, 102 were male and 48 were female. The incidence of DVT in male was 36.3% and in female it was 27.5%. One-fifth of the DVT patients were smokers. Thirty two patients underwent amputation of which 14 (43.7%) developed DVT. Among the DVT cases, only 3 were clinical DVT and the rest were sub-clinical. In half of the Laparotomy patients (10/20) DVT developed. About one-fourth (34/8) of the hernioplasty patients and half of the APR patients (4/8) developed DVT. The occurrence of the condition in diabetes mellitus (36.7%) and cancer (33.3%) was high. Forty percent of the obese patients developed the condition. DVT in Bangladesh is not that much rare event. Further in-depth studies are necessary to extract other relevant information in this regard.  JCMCTA 2015 ; 26 (2) : 29 - 33